Strategy for Strengthening Pancasila Values Through Generation Z Character Education at Madrasah Aliyah Galesong, Indonesia) - Nirwana, Nirwana; Kasmawati, Andi; Gani, Andika Wahyudi; Nasuhan, Najamuddin (Universitas of Muhammadiyah Makassar, 2025)
Generation Z, who are very close to digital technology, are often exposed to global values and cultures that can affect their understanding of local values such as Pancasila. This study aims to analyze effective learning strategies in integrating Pancasila values in Madrasah Aliyah students. This type of research is descriptive research by interviewing 15 informants at Madrasah Aliyah Babussalam Galesong. The data collection techniques in this study are observation, interviews, and documentation. As well as using the data triangulation technique of source triangulation. The results show three main strategies: moral formation, the use of technology, and the teacher's approach as a peer. This strategy is effective in increasing the strengthening of Pancasila values in Generation Z.